THE CAUSAL RELATIONSHIP BETWEEN CORRUPTION AND POVERTY IN ASEAN: A GENERAL METHOD OF MOMENTS/ DYNAMIC PANEL DATA ANALYSIS - Ina Purwantini Rahayu; Tri Widodo (Journal of Economics, Business, and Accountancy Ventura, 2012)
It has been noted by public that corruption is a practice that can be considered an extra ordinarycrime that has happened in developing countries. Such a common misuse of publicaffair is conducted for private gain, including but not limited to: corruption, nepotism, bribery,extortion, influence peddling and fraud. In Indonesia, corruption has been around foryears and increased dramatically in recent years. It distorts markets and the allocation ofresources. This research examines the Granger causal relationship between corruption andpoverty with panel data of 9 ASEAN countries during the period of observation 2005-2009. Ituses the generalized method of moments/dynamic panel data (GMM/DPD) and focuses oncapability poverty using human development index (HDI). The major results show that povertydoes not affect corruption meanwhile corruption causes poverty. There is unidirectionalcausality, from corruption to poverty.